El cuerpo y la personalidad como experiencia del ser humano (2021)
The following article presents a theoretical reflection about the vision of the body and personality as a subjective experience of the human being, this reflection being based on a bibliographic analysis. The conception of the body is analyzed from perspectives that see it as an essential part of the individual. The body as a subject, being a totality of what being is and not just a part of it. When approaching the body, one delves into the issues of experience and personality, since when incarnating the body itself, the present will be attended to from what emerges before the senses, the obvious, the experience, which is given by the relationship of body and world. It is the experience that gives clarity of what is being, since it is only possible to be completely in the present and it is from the present that the experience occurs. We are based on what we experience, and we also experience based on who we are, in other words, based on our personality; seeing again the connection between the different topics addressed in the article